Going online: an analysis of shifts in journalism practice in the Mail & Guardian’s history of digitisation - Balliah, Dinashree (My University, 2021)
The purpose of this study which focused on the South African newspaper, the Mail & Guardian (M&G), was to explore how a small to medium sized newsroom has negotiated its digital transition over the course of its history. The study used a triangulation of methods approach within the theoretical tradition of newsroom sociology. The methods of newsroom ethnography and autoethnography are included in the study to render a more nuanced picture of a local newsroom in transition as an attempt to avoid a generalised discussion which typifies traditional journalism studies. The main finding of this study is that the M&G has bungled its digital transition at the most crucial of times and has instead remained committed to the print newspaper despite the obvious global decline of the latter. The result is a news organisation left in financial limbo as it appears unable to sustain its print offering but lacks a strong enough digital offering in order to monetise its online publishing effectively. One of the conclusions drawn from this study, which also looked at the intersection between the practice of journalism and the teaching of it, is that the teaching hospital model needs interrogation and introspection. The model has always taken its lead from the industry for direction on what should be taught at the higher education level. But, in the current difficult climate for journalism, this pedagogical approach may need to embrace the idea that journalism education should become a site of innovation instead of waiting on a fractured industry to set the agenda. As we push for innovation and experimentation in the industry, so we must in spaces where journalism is taught.
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy in Journalism and Media Studies